Synthesis and Two‐Dimensional Chiral Surface Self‐Assembly of a π‐Conjugated System with Three‐Fold Symmetry: Benzotri(7‐Azaindole). Issue 4 (14th December 2020) - Rodríguez, Luis M.; Gómez, Paula; Más‐Montoya, Miriam; Abad, José; Tárraga, Alberto; Cerdá, Jorge I.; Méndez, Javier; Curiel, David
Abstract: The synthesis of a novel expanded π‐conjugated system, namely benzotri(7‐azaindole), BTAI, is reported. Its C 3 h symmetry along with the integration of six complementary donor and acceptor N−H⋅⋅⋅N hydrogen bonds in the conjugated structure promote the 2D self‐assembly on Au(111) over extended areas. Besides, a perfect commensurability with the gold lattice endows the physisorbed molecular film with a remarkable stability. The structural features of BTAI result in two levels of surface chirality: Firstly, the molecules become chiral upon adsorption on the surface. Then, due to the favorable N−H⋅⋅⋅N hydrogen bond‐directed self‐assembly, along with the relative molecular rotation with respect to the substrate, supramolecular chirality manifests in two mirror enantiomorphous domains. Thus, the system undergoes spontaneous chiral resolution. LEED and STM assisted by theoretical simulations have been employed to characterize in detail these novel 2D conglomerates with relevant chiral properties for systems with C 3 h symmetry. Abstract : The synthesis of benzotri(7‐azaindole), BTAI, aims at the control of molecular arrangement in the nanoscale. The rational design and location of hydrogen bond donor and acceptor sites promotes the two‐dimensional self‐assembly of this novel conjugated system with C 3 h symmetry. STM experiments on Au(111) and computational models prove the formation of extended homochiral domains resulting from the spontaneous resolution of the surface enantiomers.